Participation in virtual communities: online and offline life - Milinković, Marija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2015)
The purpose of the research is to establish the consequences of participation in virtual communities on the life in the physical world among electronically literate individuals. In the paper, possibilities and threats of one’s presence in online communities are presented, and observed from a sociological and psychological perspective of influence on the life in a group and individual changes. Data collection techniques conducted for the research include online questionnaire with scales of assessment aimed for measuring the intensity of attitudes and behavior on a selected sample of 100 respondents, 20 semi-structured in-depth interviews on a stratified random sample of primary and secondary school children, as well as systematic observation of image creation through the photos on virtual profiles on the sample of 238 members of Facebook. Internet made possible for everyone to become a public figure, and with that, the image that we send to others became a better version of us. The results of the research confirmed the hypothesis that life in virtual communities is equally realistic and sometimes stronger than events in the physical world. Hypotheses that are also confirmed relate to the feeling of frustration and competition on social networks, change of identity and behavior on the network. The hypothesis which claims that the youth spend more time in virtual communities, rather than in traditional ones is not confirmed in this study. The conclusion derived from comparisons of the author’s and existing research in the field of virtual communities points to the necessity of education and assistance from the education system, in odrer to prepare new generations not only for the technological understanding of virtual live, but also for recognition of its influence on offline life.
Keywords: Facebook; internet; virtual communities; cyber sociology; cyber psychology